Automated immunochemistry. Issue 7 (July 1990) - MaWhinney, W H; Warford, A; Rae, M J; Lauder, I
Abstract : A prototype immunostainer, featuring totally enclosed slide chambers, a reagent carousel and a microcomputer controlled fluid transfer system, was developed. The machine offers total flexibility in choice of primary and detection reagents for each slide and has been successfully used for the immunochemical demonstration of a variety of antigens in paraffin wax and blood smear preparations. It is considerably cheaper to use than manual immunochemistry and will be even cheaper in a production version currently under development.